Actual and simulated weather data to evaluate wet bulb globe temperature and heat index as alerts for occupational heat-related illness. Issue 1 (2nd January 2019) - Morris, Courtney E.; Gonzales, Richard G.; Hodgson, Michael J.; Tustin, Aaron W.
Abstract: Heat stress occupational exposure limits (OELs) were developed in the 1970s to prevent heat-related illnesses (HRIs). The OELs define the maximum safe wet bulb globe temperature (WBGT) for a given physical activity level. This study's objectives were to compute the sensitivity of heat stress OELs and determine if Heat Index could be a surrogate for WBGT. We performed a retrospective analysis of 234 outdoor work-related HRIs reported to the Occupational Safety and Health Administration in 2016. Archived NOAA weather data were used to compute each day's maximum WBGT and Heat Index. We defined the OELs' sensitivity as the percentage of incidents with WBGT > OEL. Sensitivity of the OELs was between 88% and 97%, depending upon our assumption about acclimatization status. In fatal cases, the OELs' sensitivity was somewhat higher (92–100%). We also computed the sensitivity of each possible Heat Index discrimination threshold. A Heat Index threshold of 80 °F (26.7 °C) was exceeded in 100% of fatalities and 99% of non-fatal HRIs. In a separate analysis, we created simulated weather data to assess associations of WBGT with Heat Index over a range of realistic outdoor heat conditions. These simulations demonstrated that for a given Heat Index, when radiant heat was included, WBGT was often higher than previously reported. The imperfect correlation between WBGT and Heat Index precluded a direct translation of OELs from WBGT into Heat Index. We conclude that WBGT-based heat stress exposure limits are highly sensitive and should be used for workplace heat hazard assessment. When WBGT is unavailable, a Heat Index alert threshold of approximately 80 °F (26.7 °C) could identify potentially hazardous workplace environmental heat.